Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ajmg.a.38245
|View full text |Cite
|
Sign up to set email alerts
|

Lissencephaly: Expanded imaging and clinical classification

Abstract: Lissencephaly (“smooth brain”, LIS) is a malformation of cortical development associated with deficient neuronal migration and abnormal formation of cerebral convolutions or gyri. The LIS spectrum includes agyria, pachygyria, and subcortical band heterotopia. Our first classification of LIS and subcortical band heterotopia (SBH) was developed to distinguish between the first two genetic causes of LIS – LIS1 (PAFAH1B1) and DCX. However, progress in molecular genetics has led to identification of 19 LIS-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
138
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(162 citation statements)
references
References 74 publications
5
138
1
6
Order By: Relevance
“…We next searched our large brain-malformation databases ($3,300 subjects) and identified the same pattern in another five children for a total of eight, including monozygotic twin sisters and one previously reported Japanese girl (Figures 1, 2, S1, and S2). 4 Phenotype According to our revised classification system for LIS, 5 the cortical malformation consists of diffuse pachygyria with thick cortex and a mild posterior gradient more severe than the anterior gradient; it varied from ''thin'' LIS with mildly thick cortex (7-10 mm) in six of eight individuals to classic LIS with very thick cortex (10-15 mm) in two of eight individuals. We found thin anterior commissures and mildly dysplastic hippocampi in all eight individuals and mildly thin corpus callosum in six of eight subjects.…”
mentioning
confidence: 99%
“…We next searched our large brain-malformation databases ($3,300 subjects) and identified the same pattern in another five children for a total of eight, including monozygotic twin sisters and one previously reported Japanese girl (Figures 1, 2, S1, and S2). 4 Phenotype According to our revised classification system for LIS, 5 the cortical malformation consists of diffuse pachygyria with thick cortex and a mild posterior gradient more severe than the anterior gradient; it varied from ''thin'' LIS with mildly thick cortex (7-10 mm) in six of eight individuals to classic LIS with very thick cortex (10-15 mm) in two of eight individuals. We found thin anterior commissures and mildly dysplastic hippocampi in all eight individuals and mildly thin corpus callosum in six of eight subjects.…”
mentioning
confidence: 99%
“…30 which was modified recently. 1,11 Taken together, this study identified a de novo nonsense mutation (c.265C > T, p.R89 Ã ) of PAFAH1B1 in an affected infant with seizures, cerebral palsy, and speech impairment. The spectrum of the clinical manifestations in this case is consistent with previous experience that agyria-pachygyria complex is associated with epilepsy, developmental delay, and motor deficits.…”
Section: Discussionmentioning
confidence: 61%
“…For instance, the Risk Adjustment for Congenital Heart Surgery (RACHS‐1) method, the Aristotle score, and the Society of Thoracic Surgeons‐European Association for Cardio‐Thoracic Surgery (STS‐EACTS) mortality score all evaluate complexity of congenital heart defects for assessment of surgical risk and outcomes (Jenkins et al, ; Lacour‐Gayet et al, ; O'Brien et al, ). Similarly, Di Donato et al have developed an imaging‐based classification system for lissencephaly, Yao et al have proposed an objective severity scale for unilaterial cleft lip, and numerous grading scales have been in used in clinical settings to assess severity of clubfoot (Catterall, ; Di Donato et al, ; Dimeglio, Bensahel, Souchet, Mazeau, & Bonnet, ; Harrold & Walker, ; Ponseti & Smoley, ; Yao et al, ). However, to our knowledge there is no existing comprehensive and objective mechanism to classify severity across all of the congenital defects.…”
Section: Discussionmentioning
confidence: 99%
“…grading scales have been in used in clinical settings to assess severity of clubfoot (Catterall, 1991;Di Donato et al, 2017;Dimeglio, Bensahel, Souchet, Mazeau, & Bonnet, 1995;Harrold & Walker, 1983;Ponseti & Smoley, 1984;Yao et al, 2019). However, to our knowledge there is no existing comprehensive and objective mechanism to classify severity across all of the congenital defects.…”
Section: Discussionmentioning
confidence: 99%